2005
DOI: 10.1007/s00586-005-1024-1
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of reliability of impedance measurement to detect iatrogenic initial pedicle perforation (in the porcine model)

Abstract: Accidental perforation of the vertebral pedicle wall is a well-known complication associated with standard approach of pedicle screw insertion. Depending on detection criteria, more than 20% of screws are reported misplaced. Serious clinical consequences, from dysesthesia to paraplegia, although not common, may result from these misplaced screws. Many techniques have been described to address this issue such as somatosensory evoked potentials, electromyography, surgical navigation, etc. Each of these technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 18 publications
1
35
0
Order By: Relevance
“…Researchers have reported the false-negative results as high as 23% using EMG monitoring method during PS placement. 18,19 With the development of computer technology, imageguidance in the spine has become an interactive and effective navigation method. Computer-aided stereotactic navigation can provide a three-dimensional (3-D) guide for PS placement.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have reported the false-negative results as high as 23% using EMG monitoring method during PS placement. 18,19 With the development of computer technology, imageguidance in the spine has become an interactive and effective navigation method. Computer-aided stereotactic navigation can provide a three-dimensional (3-D) guide for PS placement.…”
Section: Introductionmentioning
confidence: 99%
“…Initial studies carried out using a large animal model confirmed that the electrical conductivity variation detection capability of this device offers a potentially simple technique to detect pedicle perforations, prior to inserting the screw [4]. A multi-centre trial was undertaken for clinical validation.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, established guidelines recommend monitoring for personnel who are exposed to greater than 10% of the maximum permissible annual whole-body dose. 21,28,29 Given a permissible whole--body dose of 5000 mrem per year, the levels of radiation exposure documented in this study would place many spine surgeons above this 10% limit.…”
Section: Descriptores: Fluoroscopía Tornillos óSeos; Columna Vertebrmentioning
confidence: 92%
“…The electrical impedance changes as the instrument passes through cancellous and cortical bone as well as soft tissue. 21 When the electrical impedance at the tip of the PediGuard changes, the surgeon is alerted to this change via audible and visual means. The PediGuard is used in an anticipatory function during drilling of the vertebral pedicle.…”
Section: Methodsmentioning
confidence: 99%